2007
DOI: 10.2147/tcrm.2007.3.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of autoimmune bullous diseases

Abstract: Autoimmune bullous diseases result from an immune response to molecular components of the desmosome or basement membrane. Bullous diseases are associated with a high degree of morbidity and occasional mortality. Therapy of bullous diseases consists of suppressing the immune system, controlling inflammation and improving healing of erosions. The therapeutic agents used in the treatment of bullous diseases may be associated with high morbidity and occasional mortality. Successful treatment requires understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 145 publications
(167 reference statements)
0
14
0
1
Order By: Relevance
“…1 Dapsone has also been used in the treatment of the autoimmune bullous diseases (AIBD), a group of disorders resulting from autoimmunity directed against basement membrane and/or intercellular adhesion molecules on cutaneous and mucosal surfaces. 2 This review will summarize the published data evaluating dapsone as a therapy for the AIBD. Common adverse effects of this medication include methemoglobinemia and anemia, particularly in patients who are G6PD deficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Dapsone has also been used in the treatment of the autoimmune bullous diseases (AIBD), a group of disorders resulting from autoimmunity directed against basement membrane and/or intercellular adhesion molecules on cutaneous and mucosal surfaces. 2 This review will summarize the published data evaluating dapsone as a therapy for the AIBD. Common adverse effects of this medication include methemoglobinemia and anemia, particularly in patients who are G6PD deficient.…”
Section: Introductionmentioning
confidence: 99%
“…Common adverse effects of this medication include methemoglobinemia and anemia, particularly in patients who are G6PD deficient. There are also a number of additional rare adverse effects associated with dapsone use, most notably agranulocytosis and a hypersensitivity reaction known as the “dapsone-syndrome.” 1, 2 …”
Section: Introductionmentioning
confidence: 99%
“…These agents may cause a rapid progression of HIV; however, a short course of corticosteroids appears to be safe [7,17]. Once BP has improved clinically with no new blisters as well as a reduction in inflammation and pruritus, a careful tapering of the prednisone over approximately 4 months can be initiated according to the clinical response of the patient [18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to PV, BP may remit spontaneously and can often be treated with lower doses of immunosuppressives. 2 A Cochrane review published in 2010 did not identify any randomized controlled trials evaluating dapsone as a therapy for BP. 8 The 2009 review by Gürcan et al summarized the available case series, and concluded that there are at least six published studies encompassing 170 patients with BP who received dapsone.…”
Section: Pemphigoidmentioning
confidence: 99%